Kurikulum Pendidikan Matematika di Indonesia dan Perancis - Setiyani Setiyani; Iwan Junedi; M Mulyono (WACANA AKADEMIKA: Majalah Ilmiah Kependidikan, 2021)
The education curriculum of a country always changes periodically as a form of changing times, external and internal challenges. The curriculum is a set of rules that contain guidelines in achieving learning objectives. The quality of a nation's education is determined by the effectiveness of the curriculum that has been prepared and implemented. The purpose of this article is to find out how the curriculum trends in developed countries are represented by France and the curriculum in developing countries, namely Indonesia. The aspect that is the focus of this article is the learning of mathematics in these two countries. Based on the results of the literature review, information is obtained that there are some similarities between the two countries, such as the level of education and mathematics textbooks that focus on student activities. Some of the differences can be seen from the competency standards of graduates, the National Examination, and the objectives of learning mathematics.